Evaluating Ethical Tools. (April 2015) - Moula, Payam; Sandin, Per
Abstract This article reviews suggestions for how ethical tools are to be evaluated and argues that the concept of ethical soundness as presented by Kaiser et al. (2007) is unhelpful. Instead, it suggests that the quality of an ethical tool is determined by how well it achieves its assigned purpose(s). Those are different for different tools, and the article suggests a categorization of such tools into three groups. For all ethical tools, it identifies comprehensiveness and user‐friendliness as crucial. For tools that have reaching a decision in a democratic context as a main purpose, it identifies transparency, guiding users toward a decision and justification of the decision‐supporting mechanism. For tools that aim to engage the public, it identifies procedural fairness as essential. It also notes that the scope of use for ethical tools is limited to the same moral community, and that this feature is frequently overlooked.